Crack initiation and early propagation plane orientation of 2A12-T4 aluminum alloy under tension-torsion fatigue loading including mean tensile stress (Fracture and Structural Integrity, 2015)
The specimen fractures appearances are analyzed to investigate the effects of mean tensile stress on the fatigue crack initiation and early propagation plane orientation under axial-torsion fatigue loading for 2A12T4 aluminum alloy. The fatigue crack initiation and early propagation plane orientations are measured by optical microscope, the results of macro-analysis show that both the maximum shear stress amplitude and normal mean stress have effects on the orientations of crack initiation and propagation plane orientation, which are close to the plane of the maximum shear stress amplitude plane. With increasing the mean tensile stress, more cracks are inclined to initial and propagate on or near the maximum shear stress amplitude plane with larger normal mean stress, and the angle of deviation from the plane of maximum shear stress amplitude increases. The predicted plane orientations based on critical plane methods are compared with experimental measured results.
Keywords: Multiaxial fatigue; Mean tensile stress; Crack initiation and propagation plane; Critical plane orientation; Aluminum alloy